2020
DOI: 10.1002/mrm.28186
|View full text |Cite
|
Sign up to set email alerts
|

Multiphoton magnetic resonance in imaging: A classical description and implementation

Abstract: Funding information UC BerkeleyPurpose: To develop a classical geometric interpretation of multiphoton excitation and apply it to MRI. To investigate ways in which multiphoton excitation can enable novel imaging techniques. Theory and Methods: We present a fully geometric view of multiphoton excitation by taking a particular rotating frame transformation. In this rotating frame, we find that multiphoton excitations appear just like single-photon excitations again, and therefore, we can readily generalize conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Although their rapid dropoff in amplitude with N makes their use for imaging challenging, it may be possible to use BSSE pulses for multiband multiphoton excitation in implementations similar to those previously described. 26 However in general 𝜔 off should be increased to move multiphoton resonances outside the FOV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although their rapid dropoff in amplitude with N makes their use for imaging challenging, it may be possible to use BSSE pulses for multiband multiphoton excitation in implementations similar to those previously described. 26 However in general 𝜔 off should be increased to move multiphoton resonances outside the FOV.…”
Section: Discussionmentioning
confidence: 99%
“…However, excessive reduction of the frequency offset can produce out‐of band excitation (Figure 3B, at ωoff$$ {\omega}_{\mathrm{off}} $$ = 2.5 kHz) or move multiphoton resonances closer in B1+$$ {B}_1^{+} $$ to the single‐photon resonance (Figure 6) and potentially into the FOV. Although their rapid dropoff in amplitude with N$$ N $$ makes their use for imaging challenging, it may be possible to use BSSE pulses for multiband multiphoton excitation in implementations similar to those previously described 26 . However in general ωoff$$ {\omega}_{\mathrm{off}} $$ should be increased to move multiphoton resonances outside the FOV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An intensive review of this physics in the Rabi model can be found in reference [19]. This method has also been applied in medicine for magnetic resonance imaging [20,21]. Moreover, similar physics can also be found in other models without these energy levels, such as the nonlinear oscillator [22][23][24][25], nanomechanical resonators [26,27], and Josephson junctions [28,29].…”
mentioning
confidence: 89%
“…In our ongoing work, a specialized control board will be made to control one or more ADAPT Coils, and more complicated switching patterns could be designed to provide more optimal RF waveforms for higher RF amplitudes. Fields used for multiphoton MRI [47][48][49] and concurrently exciting multiple nuclei could also be implemented. Because the switching for each current direction does not have to be symmetrical, B 0 shimming and local B 0 gradients like in AC/DC coils [50][51][52][53] could also be produced.…”
Section: T a B L Ementioning
confidence: 99%